At the mountain's base - Sorell, Traci (Kokila, an imprint of Penguin Random House LLC, 2019)
"At the mountain's base sits a cabin under an old hickory tree. And in that cabin lives a family -- loving, weaving, cooking, and singing. The strength in their song sustains them through trials on the ground and in the sky, as they wait for their loved one, a pilot, to return from war."--Amazon.